Audio-Visual Media in Arabic Listening (Isti'mā’) Instruction: A Conceptual Library Review - Rizqa Lailatus Syafa'ah; Muhammad Afthon Ulin Nuha; Irfan Hania; Nazri Atoh (Lingu, 2026)
Purpose – This study aims to examine the concept of effectiveness from a theoretical perspective, describe the nature of audio-visual media in learning, analyze the characteristics of Arabic listening skills, identify the role of audio-visual media in supporting listening instruction, and explore the factors that facilitate its use. Design/methods/approach – This research employs a qualitative approach using a library research design with a descriptive-analytical method. Data were collected from secondary sources, including journal articles, books, and previous studies, and analyzed using content analysis through stages of data organization, thematic coding, interpretation, and synthesis. Findings – The findings indicate that effectiveness should be understood as the alignment between learning objectives, processes, and outcomes rather than as a purely empirical measure. Audio-visual media provide richer linguistic input, enhance comprehension through multimodal presentation, and improve learner motivation and engagement. Additionally, Arabic listening requires contextual exposure, repetition, and structured pedagogical support, which can be effectively facilitated by audio-visual media. Research Implications – The study highlights the importance of integrating audio-visual media into well-designed instructional strategies to optimize learning outcomes. It also provides a conceptual framework that contributes to the theoretical understanding of media use in Arabic listening instruction. However, as this study is based on literature review, further empirical research is recommended to validate and extend these findings in practical classroom settings. Purpose – This study aims to examine the concept of effectiveness from a theoretical perspective, describe the nature of audio-visual media in learning, analyze the characteristics of Arabic listening skills, identify the role of audio-visual media in supporting listening instruction, and explore the factors that facilitate its use. Design/methods/approach – This research employs a qualitative approach using a library research design with a descriptive-analytical method. Data were collected from secondary sources, including journal articles, books, and previous studies, and analyzed using content analysis through stages of data organization, thematic coding, interpretation, and synthesis. Findings – The findings indicate that effectiveness should be understood as the alignment between learning objectives, processes, and outcomes rather than as a purely empirical measure. Audio-visual media provide richer linguistic input, enhance comprehension through multimodal presentation, and improve learner motivation and engagement. Additionally, Arabic listening requires contextual exposure, repetition, and structured pedagogical support, which can be effectively facilitated by audio-visual media. Research Implications – The study highlights the importance of integrating audio-visual media into well-designed instructional strategies to optimize learning outcomes. It also provides a conceptual framework that contributes to the theoretical understanding of media use in Arabic listening instruction. However, as this study is based on literature review, further empirical research is recommended to validate and extend these findings in practical classroom settings.